Lithium ion battery, LATP solid electrolyte for positive electrode material and preparation method of LATP solid electrolyte

By using LATP solid electrolyte doped with pestiety in lithium-ion batteries, the problem of large interface impedance between the LATP electrolyte and the positive electrode material is solved, and the cycling performance and specific capacity of the battery are improved.

CN119695295APending Publication Date: 2025-03-25GUANGDONG YINA NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202411928204.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the prior art, the interface impedance between the LATP electrolyte and the cathode material is relatively large, which affects the cycling performance of lithium-ion batteries.

Method used

By mixing lithium carbonate, titanium dioxide, alumina, ammonium biphosphate and dibutium dioxide, adding alcohol solvents for dispersion, pre-sintering and secondary sintering, LATP solid electrolyte is finally pulverized.

Benefits of technology

The ionic conductivity and structural stability of LATP solid electrolyte are improved, the reaction with liquid electrolyte is reduced, the compatibility with electrolyte is enhanced, and the circulation performance of lithium-ion batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695295A_ABST
    Figure CN119695295A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion battery, an LATP solid electrolyte for a positive electrode material and a preparation method of the LATP solid electrolyte, and the preparation method comprises the following steps: mixing lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate and lutetium trioxide to obtain mixed powder; adding an alcohol solvent into the mixed powder to obtain mixed slurry; dispersing the mixed slurry to obtain dispersed slurry; drying the dispersed slurry to obtain a precursor; pre-sintering the precursor to obtain a pre-sintered body; carrying out secondary sintering on the pre-sintered body to obtain a solid electrolyte sintered body; and crushing the solid electrolyte sintered body to obtain the LATP solid electrolyte. The skeleton of the structure is expanded by doping lutetium in the LATP solid electrolyte, so that the ionic conductivity and the structural stability of the prepared LATP solid electrolyte are improved, and the compatibility with the electrolyte is improved; the lutetium is doped to replace Al and Ti, so that the attraction to lithium ions is reduced, and the impedance of the LATP solid electrolyte is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of lithium batteries, and in particular to a lithium-ion battery, a LATP solid electrolyte for a positive electrode material, and a preparation method thereof. Background Art

[0002] The positive electrode material in lithium-ion batteries is a key material that determines the energy density and cost of the battery, and its cost accounts for more than 30% of the total cost of the power battery. Due to the limitations of the positive electrode material itself, excessive lithium desorption under high voltage leads to unstable layered structure and rapid capacity decay, which makes the volume change of the positive electrode material structure affect the surface structure change, thereby causing side reactions at the interface of the positive electrode material, and then leading to battery failure problems such as reduced thermal stability and safety performance.

[0003] Therefore, LATP electrolyte can be used as a coating material for lithium battery positive electrode materials to effectively promote the charge transfer and transmission of lithium ions on the positive electrode materials, thereby improving the battery's cycle performance and specific capacity in practical applications. However, when LATP electrolyte has poor compatibility with the electrolyte, the interface impedance between LATP electrolyte and the positive electrode material is large, which affects the cycle performance of the lithium battery.

[0004] For example, a method for synthesizing lithium aluminum titanium phosphate disclosed in the reference document CN202310994374.9 is to preliminarily mix the materials by wet and dry grinding, and the mixture is sintered at low temperature in a graphite plate, a graphite crucible, or a ceramic sagger to obtain a precursor that can be quickly separated from the sagger, and the foreign matter contaminated on the surface of the precursor is cleaned and then wet-grinded to mix the powder for a second time, filter and dry, and perform high-temperature secondary sintering. The secondary sintering can use a conventional ceramic sagger, so that the sintered product is high, easy to demould, and the reaction is uniform. However, this scheme fails to reduce the ionic conductivity of the LATP electrolyte and the positive electrode material, thereby reducing the interface impedance between the LATP electrolyte and the positive electrode material.

[0005] Another example is a lithium aluminum titanium phosphate solid electrolyte material and its preparation method disclosed in the comparative document CN202010095811.X, which dissolves a soluble aluminum salt and a precipitant in water to obtain a mixed solution; the mixed solution is then placed in a reactor and heated, and the solid electrolyte sintered body is filtered, washed, and dried to obtain an AlOOH precursor; the AlOOH precursor is mixed with lithium salt, titanium salt, and phosphate salt, and then added to an ethanol medium for ball milling, and then pre-sintered and secondary molded in a dry air atmosphere to obtain a lithium aluminum titanium phosphate solid electrolyte material. This solution has a simple process and a low synthesis temperature, but it also fails to reduce the ionic conductivity of the LATP electrolyte and the positive electrode material, thereby reducing the interface impedance between the LATP electrolyte and the positive electrode material. Summary of the invention

[0006] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a lithium-ion battery with improved ionic conductivity and reduced impedance, a LATP solid electrolyte for positive electrode materials, and a preparation method thereof.

[0007] The purpose of this disclosure is achieved through the following technical solutions:

[0008] A method for preparing a LATP solid electrolyte for a positive electrode material comprises the following steps:

[0009] Mixing lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate and lutetium trioxide to obtain a mixed powder;

[0010] adding an alcohol solvent to the mixed powder to obtain a mixed slurry;

[0011] Performing a dispersion treatment on the mixed slurry to obtain a dispersed slurry;

[0012] Drying the dispersed slurry to obtain a precursor;

[0013] Pre-sintering the precursor at a temperature of 500° C. to 700° C. for a time of 2 h to 3 h to obtain a pre-sintered body;

[0014] Performing secondary sintering on the pre-sintered body, wherein the secondary sintering temperature is 800° C.-1300° C., and the secondary sintering time is 2 h-10 h, to obtain a solid electrolyte sintered body;

[0015] The solid electrolyte sintered body is crushed to obtain the LATP solid electrolyte.

[0016] In one embodiment, before mixing lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate and lutetium trioxide to obtain a mixed powder, the following steps are also included:

[0017] The lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate and lutetium trioxide are ball-milled separately.

[0018] In one embodiment, the amount of lutetium trioxide added is 0.5%-3%.

[0019] In one embodiment, the mixed slurry is dispersed to obtain a dispersed slurry, comprising the following steps:

[0020] The mixed slurry is subjected to microwave-assisted ball milling, the heating temperature of the microwave-assisted ball milling is 50° C.-80° C., and the ball milling time is 4 h-10 h.

[0021] In one embodiment, before the mixed slurry is subjected to microwave-assisted ball milling, an alcohol solvent is added to the mixed powder, and after the mixed slurry is obtained, the following steps are further included:

[0022] The mixed slurry is subjected to ultrasonic dispersion, and the dispersion time is 30 min-60 min.

[0023] In one embodiment, the alcohol solvent is at least one of ethanol, isopropanol and propanol.

[0024] In one embodiment, crushing the solid electrolyte sintered body to obtain the LATP solid electrolyte comprises the following steps:

[0025] Rolling the solid electrolyte sintered body;

[0026] The solid electrolyte sintered body after rolling is subjected to air flow milling to obtain the LATP solid electrolyte.

[0027] In one embodiment, the pulverizing pressure of the air flow pulverization is 0.4MPa-0.9MPa, and the particle size D50 of the LATP solid electrolyte is 200nm-300nm.

[0028] A LATP solid electrolyte for a positive electrode material is prepared by using the preparation method of the LATP solid electrolyte for a positive electrode material described in any of the above embodiments.

[0029] A lithium-ion battery comprises a negative electrode sheet, a positive electrode sheet and a separator located between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet contains a positive electrode material, and the positive electrode material contains the LATP solid electrolyte for the positive electrode material described in any of the above embodiments.

[0030] Compared with the prior art, the present invention has at least the following advantages:

[0031] The lithium-ion battery, the LATP solid electrolyte for positive electrode materials and the preparation method thereof, disperse the mixed powder with an alcohol solvent so that the particles of each powder in the obtained precursor are evenly dispersed, which is conducive to the sintering reaction of the precursor; through high-temperature secondary sintering, lutetium trioxide is fully combined with lithium carbonate, titanium dioxide, aluminum oxide and ammonium hydrogen phosphate, so that the structure of the obtained lutetium-doped LATP solid electrolyte is more stable;

[0032] By doping LATP solid electrolyte with lutetium, lutetium expands the skeleton of the LATP solid electrolyte structure, thereby broadening the transmission channel of lithium ions, thereby improving the ionic conductivity and structural stability of the prepared LATP solid electrolyte, thereby reducing its reaction with components in the liquid electrolyte and improving its compatibility with the electrolyte; by incorporating lutetium to replace Al and Ti, the attraction to lithium ions is reduced, which is beneficial to the migration of lithium ions in the LATP structure, further reducing the impedance of the LATP solid electrolyte, and thereby improving the cycle performance of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present disclosure and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 A flowchart of a method for preparing a LATP solid electrolyte according to an embodiment of the present invention;

[0035] Figure 2 is a curve chart of the capacity retention rate of the lithium battery manufactured in Example 1;

[0036] Figure 3 is a curve chart of the capacity retention rate of the lithium battery produced in Example 2;

[0037] Figure 4 is a curve chart of the capacity retention rate of the lithium battery manufactured in Example 3;

[0038] Figure 5 A curve chart showing the capacity retention rate of the lithium battery produced in Comparative Example 1;

[0039] Figure 6 It is a curve chart of the capacity retention rate of the lithium batteries prepared in Examples 4-6 and Comparative Example 4;

[0040] Figure 7 FIG. 1 is a scanning electron microscope image of a LATP solid electrolyte according to an embodiment. DETAILED DESCRIPTION

[0041] In order to facilitate the understanding of the present disclosure, the present disclosure will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present disclosure are given in the drawings. However, the present disclosure can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present disclosure more thoroughly and comprehensively understood.

[0042] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.

[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present disclosure. The terms used herein in the specification of the present disclosure are only for the purpose of describing specific embodiments and are not intended to limit the present disclosure. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0044] In order to better understand the technical solutions and beneficial effects of the present invention, the present invention is further described in detail below in conjunction with specific embodiments:

[0045] The present application provides a method for preparing a LATP solid electrolyte for positive electrode materials. The above-mentioned method for preparing the LATP solid electrolyte comprises the following steps: mixing lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate and lutetium trioxide to obtain a mixed powder; adding an alcohol solvent to the mixed powder to obtain a mixed slurry; dispersing the mixed slurry to obtain a dispersed slurry; drying the dispersed slurry to obtain a precursor; pre-sintering the precursor, the pre-sintering temperature is 500℃-700℃, the pre-sintering time is 2h-3h, to obtain a pre-sintered body; secondary sintering the pre-sintered body, the secondary sintering temperature is 800℃-1300℃, the secondary sintering time is 2h-10h, to obtain a solid electrolyte sintered body; crushing the solid electrolyte sintered body to obtain the LATP solid electrolyte.

[0046] See also Figure 1 , which is a method for preparing a LATP solid electrolyte for a positive electrode material according to an embodiment of the present invention, comprising the following steps:

[0047] S101: Mix lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate and lutetium trioxide to obtain a mixed powder. In this embodiment, lutetium, as a rare earth element, has a strong ionic polarity and a large ionic radius. Lutetium can chemically interact with other components in LATP, such as Ti, Al, etc., and a LATP solid electrolyte doped with lutetium can be formed by mixing lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate and lutetium trioxide and sintering. The rare earth element lutetium can expand the skeleton of the LATP structure, so that the transmission channel of lithium ions is widened, thereby improving the ionic conductivity of the LATP solid electrolyte. Since the electronegativity of lutetium is lower than that of Al and Ti, the lutetium element is doped in the LATP solid electrolyte to replace Al and Ti elements, so that the electronegativity difference between oxygen and metals with lower electronegativity will increase, so that more electrons are attached to O at the octahedral corner of the LATP solid electrolyte, increasing the repulsive force of adjacent octahedrons of the LATP solid electrolyte, resulting in the weakening of the attraction of the LATP solid electrolyte to the lithium ions in the cage, which is conducive to the migration of lithium ions in the LATP structure.

[0048] S103: adding an alcohol solvent to the mixed powder to obtain a mixed slurry. In this embodiment, the alcohol solvent is added to the mixed powder so that the mixed powder forms a uniform suspension solution in the alcohol solvent. Alcohol molecules have strong polarity and are easy to form hydrogen bonds and other interaction forces with other molecules, thereby reducing surface tension. The low surface tension of the alcohol solvent helps the alcohol solvent to better cover and penetrate during the dispersion process, thereby making it easier for the alcohol solvent to wet and disperse the mixed powder.

[0049] S105: Dispersing the mixed slurry to obtain dispersed slurry. In this embodiment, dispersing the mixed slurry improves the mixing uniformity of the powders, reduces the particle size of the powders in the mixed slurry, and increases the specific surface area, which is beneficial to the chemical reaction between the powders and improves the sintering activity, thereby obtaining a denser sintered body.

[0050] S107: Dry the dispersed slurry to obtain a precursor. In this embodiment, the alcohol solvent in the dispersed slurry is removed by drying, so that the precursor in the slurry is concentrated and fixed, thereby reducing the influence of the alcohol solvent on the sintering of the precursor.

[0051] S109 pre-sintering the precursor at a sintering temperature of 500° C.-700° C. to obtain a pre-sintered body. In this embodiment, by pre-sintering the precursor, AlPO4 impurities are reduced or removed, thereby greatly reducing impurities in the pre-sintered body. During pre-sintering, gas molecules in the precursor can also be removed, thereby reducing the gaps between the powder particles in the precursor, and the powder particles in the precursor are more likely to react to form a solid electrolyte during the sintering process.

[0052] S111 performs secondary sintering on the pre-sintered body, and the sintering temperature is 800° C.-1300° C. to obtain a solid electrolyte sintered body. In this embodiment, the sintering temperature is 800° C.-1300° C., so that lutetium trioxide is more easily reacted and combined with lithium carbonate, titanium dioxide, aluminum oxide and ammonium hydrogen phosphate, thereby obtaining a stable lutetium-doped solid electrolyte sintered body.

[0053] S113 crushes the solid electrolyte sintered body to obtain LATP solid electrolyte. In this embodiment, after the solid electrolyte sintered body is crushed, the particle size of LATP solid electrolyte is small, and the specific surface area is increased, thereby increasing the contact area with the positive electrode material, and more contact points increase the ion transmission channel, thereby reducing the interface impedance between the LATP solid electrolyte and the positive electrode, thereby improving the charge and discharge efficiency of the prepared lithium ion battery.

[0054] The preparation method of the LATP solid electrolyte for positive electrode materials is as follows: by dispersing the mixed powder with an alcohol solvent, the particles of each powder in the obtained precursor are evenly dispersed, which is beneficial to the sintering reaction of the precursor; by secondary sintering at high temperature, lutetium trioxide is fully combined with lithium carbonate, titanium dioxide, aluminum oxide, and ammonium hydrogen phosphate, so that the structure of the obtained lutetium-doped LATP solid electrolyte is more stable; by doping lutetium in the LATP solid electrolyte, lutetium expands the skeleton of the LATP solid electrolyte structure, thereby broadening the transmission channel of lithium ions, thereby improving the ionic conductivity and structural stability of the prepared LATP solid electrolyte, thereby reducing its reaction with the components in the liquid electrolyte and improving its compatibility with the electrolyte; by incorporating lutetium to replace Al and Ti, the attraction to lithium ions is reduced, which is beneficial to the transition of lithium ions in the LATP structure, further reducing the impedance of the LATP solid electrolyte, and thus improving the cycle performance of the lithium-ion battery.

[0055] Further, in one of the embodiments, during the pre-sintering heating process, the pre-sintering heating rate is 1°C / min-8°C / min. In this embodiment, during the pre-sintering heating process, the molecular gas in the precursor overflows from the precursor. When the molecular gas overflows too fast, the structure of the precursor is destroyed, resulting in a large number of pores. The pores are not conducive to the contact between lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate and lutetium trioxide particles, resulting in too many impurities in the obtained pre-sintered body. Specifically, the pre-sintering heating rate is 2°C / min, the molecular gas of the precursor overflows from the precursor at a slow rate, and the structure of the precursor is less damaged, so that the obtained pre-sintered body has fewer impurities, the prepared LATP solid electrolyte has fewer impurities, and the battery prepared by the LATP solid electrolyte has a better capacity retention rate.

[0056] Furthermore, in one of the embodiments, when the precursor is pre-sintered, the heating rate of the secondary sintering is 20°C / min-40°C / min during the heating process of the pre-sintered body for secondary sintering. It can be understood that after the precursor is pre-sintered, the gaseous substances in the precursor have completely overflowed, and increasing the heating rate will not cause pores in the pre-sintered body; during the secondary sintering, the heating rate of sintering is increased to 20°C / min-40°C / min, and the sintering temperature is rapidly increased from 500°C-700°C to 800°C-1300°C, so that the sintering activity and material diffusion rate are accelerated, thereby causing the rapid growth of grains during the sintering process, thereby improving the compactness of the solid electrolyte sintered body, and improving the mechanical strength and ionic conductivity of the LATP solid electrolyte after the solid electrolyte sintered body is crushed.

[0057] In one of the embodiments, after the precursor is pre-sintered, during the heating process of the pre-sintered body for secondary sintering, if the difference between the preset secondary sintering temperature of the secondary sintering and the pre-sintering temperature is greater than 200°C, the preset heating rate of the secondary sintering is increased by 5°C / min; if the difference between the preset secondary sintering temperature of the secondary sintering and the pre-sintering temperature is less than or equal to 200°C, the preset heating rate of the secondary sintering remains unchanged.

[0058] In this embodiment, the preset secondary sintering temperature of the secondary sintering is the optimal sintering temperature of 900°C. When the difference between the preset secondary sintering temperature of the secondary sintering and the pre-sintering temperature is less than or equal to 200°C, the heating rate remains unchanged, so that the secondary sintering maintains a faster sintering efficiency, thereby improving the density of the solid electrolyte sintered body; by increasing the preset heating rate of the secondary sintering, the temperature of the secondary sintering reaches the predetermined secondary sintering temperature more quickly, thereby shortening the entire secondary sintering time, thereby improving the sintering efficiency of the secondary sintering, and further improving the density of the solid electrolyte sintered body through a faster heating rate.

[0059] In one embodiment, before mixing lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate and lutetium trioxide to obtain a mixed powder, the following steps are also included:

[0060] The lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate and lutetium trioxide are mixed and separately ball-milled. In the present embodiment, lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate and lutetium trioxide are not easy to disperse in the subsequent mixed slurry, therefore, they are firstly separately ball-milled, so that the particle size of lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate and lutetium trioxide is reduced, thereby reducing the difficulty of subsequent dispersion treatment of lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate and lutetium trioxide, and also saving processing time, which is conducive to improving the uniformity between lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate and lutetium trioxide.

[0061] In one of the embodiments, the amount of lutetium trioxide added is 0.5%-3%. In this embodiment, as the amount of lutetium trioxide added increases, the ionic conductivity of the battery made of LATP solid electrolyte first increases and then decreases. When the amount of lutetium trioxide added is less than 0.5%, due to the small amount of doping, the lutetium is limited in expanding the skeleton of the LATP solid electrolyte, so the ionic conductivity of the battery is not significantly improved. When the amount of lutetium trioxide added is greater than 3%, due to the excessive amount of doping, the leaching structure of the LATP solid electrolyte is greatly deformed, which has an adverse effect on the overall conductivity; when the amount of lutetium trioxide added is 0.5%-3%, the ionic conductivity of the battery made of the obtained LATP solid electrolyte is higher and the impedance is lower.

[0062] Furthermore, in one of the embodiments, the ratio of Li2CO3, TiO2, Al2O3, NH4H2PO4 and Lu2O3 in the mixed powder is 1.2-1.3: 3.2-3.6: 0.2-0.4: 5-7: 0.055-0.22. In this embodiment, different LATP solid electrolytes are obtained by mixing different Li2CO3, TiO2, Al2O3, NH4H2PO4 and Lu2O3, so as to meet the requirements of different lithium battery positive electrode materials for LATP solid electrolytes.

[0063] In one embodiment, the mixed slurry is dispersed to obtain a dispersed slurry, comprising the following steps:

[0064] The mixed slurry is subjected to microwave-assisted ball milling, the heating temperature of the microwave-assisted ball milling is 50°C-80°C, and the ball milling time is 4h-10h. In this embodiment, the heat generated by friction and collision during the traditional ball milling process may cause local overheating, form a thermal gradient, and affect the quality and performance of the solid electrolyte sintered body. Microwave-assisted ball milling utilizes the penetration and selective heating characteristics of microwaves to uniformly heat the powder particles by microwaves to reduce the influence of overheating or thermal gradient of the powder particles. The powder particles are heated to 50°C-80°C, so that the powder particles are dispersed at a suitable temperature, and the particle morphology of the powder in the mixed slurry is improved. The mixed slurry is ball milled for 4h-10h, so that the lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate and lutetium trioxide in the mixed slurry are fully dispersed and uniform, thereby making the powder particles in the precursor more uniform, which is conducive to full contact of the powder in the precursor.

[0065] In one embodiment, before the mixed slurry is subjected to microwave-assisted ball milling, an alcohol solvent is added to the mixed powder, and before the mixed slurry is obtained, the following steps are also included:

[0066] The mixed slurry is ultrasonically dispersed, and the dispersion time is 30min-60min. In this embodiment, when lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate and lutetium trioxide are mixed with an alcohol solvent, lutetium is more likely to chemically interact with Ti or Al in other components to form agglomerates due to its strong ionic polarity and large ionic radius. Ultrasound can disperse and homogenize the raw material particles, improve the uniformity of the slurry, and break the agglomeration between lutetium trioxide particles through ultrasonic dispersion, so that lutetium trioxide is more evenly distributed in the mixed slurry.

[0067] In one embodiment, the alcohol solvent is at least one of ethanol, isopropanol and propanol. In this embodiment, the boiling points of ethanol, isopropanol and propanol are relatively low, so that the alcohol solvent evaporates quickly during drying, so that the dispersion slurry dries quickly in the oven, thereby accelerating the drying process and avoiding the residue of the alcohol solvent. Further, when the dispersion slurry is dried, the dispersion slurry is dried in a vacuum. Drying in a vacuum drying oven prevents the contamination of the dispersion slurry by impurities in the air during the drying process, thereby making the obtained precursor purer and avoiding the influence of the residual alcohol solvent on the sintering process.

[0068] In one embodiment, the pulverizing of the solid electrolyte sintered body to obtain the LATP solid electrolyte comprises the following steps:

[0069] Rolling the solid electrolyte sintered body;

[0070] The solid electrolyte sintered body after rolling is subjected to air flow crushing to obtain the LATP solid electrolyte. In this embodiment, the solid electrolyte sintered body is deformed and broken into uniform particles by rolling the roller machine, the gap of the roller machine is 2mm, and the roller speed is 150r / min, so that the solid electrolyte sintered body is deformed and broken into uniform particles; by rolling the solid electrolyte sintered body, the solid electrolyte sintered body is initially crushed, so that the solid electrolyte sintered body is deformed and broken into smaller particles, reducing the difficulty of subsequent air flow crushing. By air flow crushing the solid electrolyte sintered body after rolling, the particle size of the LATP solid electrolyte is smaller. When the particle size of the LATP solid electrolyte is smaller, the interface impedance between the LATP solid electrolyte and the positive electrode is reduced, thereby improving the charge and discharge efficiency of the obtained lithium-ion battery.

[0071] In one embodiment, the pulverizing pressure of the air flow pulverizing is 0.4MPa-0.9MPa, and the particle size D50 of the LATP solid electrolyte is 200nm-300nm. In this embodiment, the collision of the LATP solid electrolyte is controlled by controlling the air pressure of the air flow pulverizing, thereby controlling the particle size of the LATP solid electrolyte. When the pulverizing pressure of the air flow pulverizing is less than 0.4MPa, the collision impact between the LATP solid electrolytes is small, so that the obtained LATP solid electrolyte particles are greater than 300nm, and the specific surface area of ​​the LATP solid electrolyte in the positive electrode material is reduced, thereby making the transmission path of lithium ions in the LATP solid electrolyte longer, thereby causing the ionic conductivity to decrease. When the pulverizing pressure of the air flow pulverizing is greater than 0.9Mpa, the collision impact between the LATP solid electrolytes is large, so that the obtained LATP solid electrolyte particles are less than 300nm, and the LATP solid electrolyte particles are added to the positive electrode material chamber, and the LATP solid electrolyte particles will form an uneven thin layer coating on the surface, resulting in unstable battery performance, and then a local short circuit of the battery.

[0072] Furthermore, when the solid electrolyte sintered body is rolled, it is rolled by a roller machine, the gap of the roller machine is 2 mm, and the roller speed is 150 r / min. The solid electrolyte sintered body is preliminarily reduced in particle size by the roller machine, so that the solid electrolyte sintered body is broken into relatively uniform particles to form solid electrolyte sintered body particles of uniform size, and then the solid electrolyte sintered body particles of uniform size are air flow crushed, so that the particle size uniformity of the precursor obtained by air flow crushing is better.

[0073] Furthermore, in one of the embodiments, the particle size of the LATP solid electrolyte cannot be precisely controlled due to the airflow pulverization.

[0074] If the particle size D50 of the LATP solid electrolyte is greater than 300 nm, perform the following steps:

[0075] Secondarily crushing the LATP solid electrolyte;

[0076] If the particle size D50 of the LATP solid electrolyte is less than 200 nm, the following steps are performed:

[0077] ball milling the LATP solid electrolyte to obtain a solid electrolyte recovery material;

[0078] Adding the solid electrolyte recovery material into the mixed slurry, wherein the addition amount of the solid electrolyte is 5%-10% of the mixed powder;

[0079] The mixed slurry is dispersed to obtain a dispersed slurry; the precursor is pre-sintered at a sintering temperature of 500°C-700°C to obtain a pre-sintered body; the pre-sintered body is secondary sintered at a sintering temperature of 800°C-1300°C to obtain a solid electrolyte sintered body; the solid electrolyte sintered body is crushed to obtain a LATP solid electrolyte.

[0080] It can be understood that when the particle D50 of the LATP solid electrolyte is greater than 300nm, the LATP solid electrolyte is subjected to secondary crushing and air flow crushing is performed at an air pressure of 0.4MPa-0.6MPa. The specific surface area of ​​the LATP solid electrolyte after secondary crushing in the positive electrode material is reduced, thereby making the transmission path of lithium ions in the LATP solid electrolyte longer, thereby resulting in a decrease in ionic conductivity, a decrease in the contact area between the LATP particles with a larger particle size and the electrode material, and an increase in the interface resistance, which affects the battery performance.

[0081] It is understandable that when the particle size D50 of the LATP solid electrolyte is less than 200nm, after the LATP solid electrolyte is ball-milled, the particle size of the solid electrolyte recycled material is further reduced, which is conducive to the mixing of the solid electrolyte recycled material and the mixed slurry. The solid electrolyte recycled material is added to the mixed slurry for dispersion and mixing, so that the precursor solid electrolyte recycled material is evenly distributed in the precursor, and the amount of solid electrolyte added to the mixed slurry is small, so that the solid electrolyte has less impact on the mixed slurry. When the solid electrolyte recycled material is pre-sintered and secondary sintered in the precursor in sequence, since the solid electrolyte recycled material has completed sintering, the state of the solid electrolyte recycled material has not changed after sintering, and the solid electrolyte recycled material is reconnected to the solid electrolyte sintered body. After the sintered clinker is crushed, the LATP solid electrolyte is obtained again, which improves the qualified output rate of the LATP solid electrolyte, thereby reducing the production cost.

[0082] The present application also provides a LATP solid electrolyte for positive electrode materials, which is prepared by the preparation method of the LATP solid electrolyte for positive electrode materials described in any of the above embodiments. In this embodiment, lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate and lutetium trioxide are mixed to obtain a mixed powder; an alcohol solvent is added to the mixed powder to obtain a mixed slurry; an alcohol solvent is added to the mixed powder to obtain a mixed slurry; the mixed slurry is dispersed to obtain a dispersed slurry; the dispersed slurry is dried to obtain a precursor; the precursor is pre-sintered at a sintering temperature of 500-700°C to obtain a pre-sintered body; the pre-sintered body is secondary sintered at a sintering temperature of 800°C-1300°C to obtain a solid electrolyte sintered body; the solid electrolyte sintered body is rolled, and the solid electrolyte sintered body after rolling is air flow crushed to obtain a LATP solid electrolyte.

[0083] By doping with lutetium, the skeleton structure of the LATP solid electrolyte is expanded, thereby broadening the transmission channel of lithium ions, thereby improving the ionic conductivity of the prepared LATP solid electrolyte; by doping with lutetium to replace Al and Ti, the attraction to lithium ions is reduced, which is beneficial to the migration of lithium ions in the LATP structure and further reduces the impedance of the LATP solid electrolyte.

[0084] The present application also provides a lithium-ion battery, comprising a negative electrode sheet, a positive electrode sheet, and a separator between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet contains a positive electrode material, and the positive electrode material contains the LATP solid electrolyte for the positive electrode material described in any of the above embodiments. In this embodiment, the LATP solid electrolyte reduces the interface impedance with the positive electrode material, improves the compatibility with the positive electrode material, thereby improving the ionic conductivity of the lithium-ion battery, and further improving the cycle performance of the lithium-ion battery.

[0085] Compared with the prior art, the present invention has at least the following advantages:

[0086] The preparation method of the LATP solid electrolyte is to disperse the mixed powder with an alcohol solvent so that the particles of each powder in the obtained precursor are evenly dispersed, which is conducive to the sintering reaction of the precursor; through high-temperature secondary sintering, lutetium trioxide is fully combined with lithium carbonate, titanium dioxide, aluminum oxide, and ammonium hydrogen phosphate, so that the structure of the obtained lutetium-doped LATP solid electrolyte is more stable;

[0087] By doping LATP solid electrolyte with lutetium, lutetium expands the skeleton of the LATP solid electrolyte structure, thereby broadening the transmission channel of lithium ions, thereby improving the ionic conductivity and structural stability of the prepared LATP solid electrolyte, thereby reducing its reaction with components in the liquid electrolyte and improving its compatibility with the electrolyte; by incorporating lutetium to replace Al and Ti, the attraction to lithium ions is reduced, which is beneficial to the migration of lithium ions in the LATP structure, further reducing the impedance of the LATP solid electrolyte, and thereby improving the cycle performance of lithium-ion batteries.

[0088] Some specific examples are listed below, and if % is mentioned, it means percentage by weight. It should be noted that the following examples do not exhaust all possible situations, and the materials used in the following examples can be obtained from commercial sources unless otherwise specified.

[0089] Example 1

[0090] Weigh lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate, and lutetium trioxide: 1.924g, 5.440g, 0.612g, 13.800g, and 0.1122g (Li2CO3:TiO2:Al2O3:NH4H2PO4:Lu2O3=1.3:3.4:0.3:6:0.11) respectively, and mix them evenly after ball milling.

[0091] 65.328 g of ethanol was added to obtain a mixed slurry, and after mixing, the raw material particles were dispersed using ultrasound for 30 min;

[0092] The mixed slurry was placed in a microwave ball mill for ball milling at a heating temperature of 70° C. to obtain a dispersed slurry;

[0093] The dispersed slurry is dried at a drying temperature of 80°C in a vacuum drying oven. Drying in a vacuum is to prevent contamination by impurities during the drying process to obtain a precursor;

[0094] The precursor was transferred to a tube furnace and pre-sintered in an air atmosphere at a temperature of 600 °C, a sintering time of 2 h, and a heating rate of 2 °C / min.

[0095] The pre-sintered body is subjected to secondary sintering at a sintering temperature of 900°C and a sintering time of 6 h;

[0096] The sintered solid electrolyte sintered body was subjected to roller pressing and air flow pulverization treatment at an air pressure of 0.7 MPa to obtain the LATP solid electrolyte.

[0097] Example 2

[0098] Weigh lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate, and lutetium trioxide: 1.924g, 5.440g, 0.612g, 13.800g, and 0.1122g (Li2CO3:TiO2:Al2O3:NH4H2PO4:Lu2O3=1.3:3.4:0.3:6:0.11) respectively, and mix them evenly after ball milling.

[0099] 65.328 g of ethanol was added to obtain a mixed slurry;

[0100] The mixed slurry is placed in a microwave ball mill for ball milling at a heating temperature of 70° C. to obtain a dispersed slurry; the dispersed slurry is dried at a drying temperature of 80° C. The drying equipment is a vacuum drying oven. Drying in a vacuum is to prevent contamination by impurities during the drying process to obtain a precursor;

[0101] The precursor was transferred to a tube furnace and pre-sintered in an air atmosphere at a temperature of 500 °C, a sintering time of 2 h, and a heating rate of 4 °C / min.

[0102] The pre-sintered body is subjected to secondary sintering at a sintering temperature of 900°C and a sintering time of 6 h;

[0103] The sintered solid electrolyte sintered body was subjected to roller pressing and air flow pulverization treatment at an air pressure of 0.7 MPa to obtain the LATP solid electrolyte.

[0104] LATP was added to LCO at a mass ratio of 0.5%, and the mixture was dry-milled to prepare CR2032 button cells as lithium battery positive electrode materials.

[0105] Example 3

[0106] Weigh lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate, and lutetium trioxide: 1.924g, 5.440g, 0.612g, 13.800g, and 0.1122g (Li2CO3:TiO2:Al2O3:NH4H2PO4:Lu2O3=1.3:3.4:0.3:6:0.11) respectively, and mix them evenly after ball milling.

[0107] 65.328 g of ethanol was added to obtain a mixed slurry;

[0108] The mixed slurry is placed in a microwave ball mill for ball milling at a heating temperature of 70° C. to obtain a dispersed slurry; the dispersed slurry is dried at a drying temperature of 80° C. The drying equipment is a vacuum drying oven. Drying in a vacuum is to prevent contamination by impurities during the drying process to obtain a precursor;

[0109] The precursor was transferred to a tube furnace and pre-sintered in an air atmosphere at a temperature of 700 °C, a sintering time of 2 h, and a heating rate of 3 °C / min.

[0110] The pre-sintered body is subjected to secondary sintering at a sintering temperature of 900°C and a sintering time of 6 h;

[0111] The sintered solid electrolyte sintered body was subjected to roller pressing and air flow pulverization treatment at an air pressure of 0.7 MPa to obtain the LATP solid electrolyte.

[0112] LATP was added to LCO at a mass ratio of 0.5%, and the mixture was dry-milled to prepare CR2032 button cells as lithium battery positive electrode materials.

[0113] Example 4

[0114] Weigh 2.401g, 6.802g, 0.602g, 10.103g and 0.111g of lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate and lutetium trioxide (Li2CO3:TiO2:Al2O3:NH4H2PO4:Lu2O3=1.2:3.4:0.3:5.05:0.05) respectively, and mix them evenly after ball milling.

[0115] 65.328 g of ethanol was added to obtain a mixed slurry, and after mixing, the raw material particles were dispersed using ultrasound for 30 min;

[0116] The mixed slurry was placed in a microwave ball mill for ball milling at a heating temperature of 70° C. to obtain a dispersed slurry;

[0117] The dispersed slurry is dried at a drying temperature of 80°C in a vacuum drying oven. Drying in a vacuum is to prevent contamination by impurities during the drying process to obtain a precursor;

[0118] The precursor was transferred to a tube furnace and pre-sintered in an air atmosphere at a temperature of 600 °C, a sintering time of 2 h, and a heating rate of 2 °C / min.

[0119] The pre-sintered body is subjected to secondary sintering at a sintering temperature of 900°C and a sintering time of 6 h;

[0120] The sintered solid electrolyte sintered body was subjected to roller pressing and air flow pulverization treatment at an air pressure of 0.7 MPa to obtain the LATP solid electrolyte.

[0121] Example 5

[0122] Weigh lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate, and lutetium trioxide: 2.402g, 6.703g, 0.604g, 10.101g, and 0.203g (Li2CO3:TiO2:Al2O3:NH4H2PO4:Lu2O3=1.2:3.35:0.3:5.05:0.1) respectively, and mix them evenly after ball milling.

[0123] 65.328 g of ethanol was added to obtain a mixed slurry, and after mixing, the raw material particles were dispersed using ultrasound for 30 min;

[0124] The mixed slurry was placed in a microwave ball mill for ball milling at a heating temperature of 70° C. to obtain a dispersed slurry;

[0125] The dispersed slurry is dried at a drying temperature of 80°C in a vacuum drying oven. Drying in a vacuum is to prevent contamination by impurities during the drying process to obtain a precursor;

[0126] The precursor was transferred to a tube furnace and pre-sintered in an air atmosphere at a temperature of 600 °C, a sintering time of 2 h, and a heating rate of 2 °C / min.

[0127] The pre-sintered body is subjected to secondary sintering at a sintering temperature of 900°C and a sintering time of 6 h;

[0128] The sintered solid electrolyte sintered body was subjected to roller pressing and air flow pulverization treatment at an air pressure of 0.7 MPa to obtain the LATP solid electrolyte.

[0129] Example 6

[0130] Weigh lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate, and lutetium trioxide: 2.402g, 6.402g, 0.504g, 10.101g, and 0.601g (Li2CO3:TiO2:Al2O3:NH4H2PO4:Lu2O3=1.2:3.2:0.25:5.05:0.3) respectively, and mix them evenly after ball milling.

[0131] 65.328 g of ethanol was added to obtain a mixed slurry, and after mixing, the raw material particles were dispersed using ultrasound for 30 min;

[0132] The mixed slurry was placed in a microwave ball mill for ball milling at a heating temperature of 70° C. to obtain a dispersed slurry;

[0133] The dispersed slurry is dried at a drying temperature of 80°C in a vacuum drying oven. Drying in a vacuum is to prevent contamination by impurities during the drying process to obtain a precursor;

[0134] The precursor was transferred to a tube furnace and pre-sintered in an air atmosphere at a temperature of 600 °C, a sintering time of 2 h, and a heating rate of 2 °C / min.

[0135] The pre-sintered body is subjected to secondary sintering at a sintering temperature of 900°C and a sintering time of 6 h;

[0136] The sintered solid electrolyte sintered body was subjected to roller pressing and air flow pulverization treatment at an air pressure of 0.7 MPa to obtain the LATP solid electrolyte.

[0137] Example 7

[0138] Weigh lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate, and lutetium trioxide: 2.402g, 6.401g, 0.401g, 10.006g, and 0.800g (Li2CO3:TiO2:Al2O3:NH4H2PO4:Lu2O3=1.2:3.2:0.2:5:0.4) respectively, and mix them evenly after ball milling.

[0139] 65.328 g of ethanol was added to obtain a mixed slurry, and after mixing, the raw material particles were dispersed using ultrasound for 30 min;

[0140] The mixed slurry was placed in a microwave ball mill for ball milling at a heating temperature of 70° C. to obtain a dispersed slurry;

[0141] The dispersed slurry is dried at a drying temperature of 80°C in a vacuum drying oven. Drying in a vacuum is to prevent contamination by impurities during the drying process to obtain a precursor;

[0142] The precursor was transferred to a tube furnace and pre-sintered in an air atmosphere at a temperature of 600 °C, a sintering time of 2 h, and a heating rate of 2 °C / min.

[0143] The pre-sintered body is subjected to secondary sintering at a sintering temperature of 900°C and a sintering time of 6 h;

[0144] The sintered solid electrolyte sintered body was subjected to roller pressing and air flow pulverization treatment at an air pressure of 0.7 MPa to obtain the LATP solid electrolyte.

[0145] Example 8

[0146] Weigh lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate, and lutetium trioxide: 1.924g, 5.440g, 0.612g, 13.800g, and 0.1122g (Li2CO3:TiO2:Al2O3:NH4H2PO4:Lu2O3=1.3:3.4:0.3:6:0.11) respectively, and mix them evenly after ball milling.

[0147] 65.328 g of ethanol was added to obtain a mixed slurry, and after mixing, the raw material particles were dispersed using ultrasound for 30 min;

[0148] The mixed slurry was placed in a microwave ball mill for ball milling at a heating temperature of 70° C. to obtain a dispersed slurry;

[0149] The dispersed slurry is dried at a drying temperature of 80°C in a vacuum drying oven. Drying in a vacuum is to prevent contamination by impurities during the drying process to obtain a precursor;

[0150] The precursor was transferred to a tube furnace and pre-sintered in an air atmosphere at a temperature of 600 °C, a sintering time of 2 h, and a heating rate of 2 °C / min.

[0151] The pre-sintered body is subjected to secondary sintering at a sintering temperature of 900°C and a sintering time of 6 h;

[0152] The sintered solid electrolyte sintered body was subjected to roller pressing and air flow pulverization treatment at an air pressure of 0.4 MPa to obtain the LATP solid electrolyte.

[0153] Example 9

[0154] Weigh lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate, and lutetium trioxide: 1.924g, 5.440g, 0.612g, 13.800g, and 0.1122g (Li2CO3:TiO2:Al2O3:NH4H2PO4:Lu2O3=1.3:3.4:0.3:6:0.11) respectively, and mix them evenly after ball milling.

[0155] 65.328 g of ethanol was added to obtain a mixed slurry, and after mixing, the raw material particles were dispersed using ultrasound for 30 min;

[0156] The mixed slurry was placed in a microwave ball mill for ball milling at a heating temperature of 70° C. to obtain a dispersed slurry;

[0157] The dispersed slurry is dried at a drying temperature of 80°C in a vacuum drying oven. Drying in a vacuum is to prevent contamination by impurities during the drying process to obtain a precursor;

[0158] The precursor was transferred to a tube furnace and pre-sintered in an air atmosphere at a temperature of 600 °C, a sintering time of 2 h, and a heating rate of 2 °C / min.

[0159] The pre-sintered body is subjected to secondary sintering at a sintering temperature of 900°C and a sintering time of 6 h;

[0160] The sintered solid electrolyte sintered body was subjected to roller pressing and air flow pulverization treatment at an air pressure of 0.7 MPa to obtain the LATP solid electrolyte.

[0161] Example 10

[0162] Weigh lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate, and lutetium trioxide: 1.924g, 5.440g, 0.612g, 13.800g, and 0.1122g (Li2CO3:TiO2:Al2O3:NH4H2PO4:Lu2O3=1.3:3.4:0.3:6:0.11) respectively, and mix them evenly after ball milling.

[0163] 65.328 g of ethanol was added to obtain a mixed slurry, and after mixing, the raw material particles were dispersed using ultrasound for 30 min;

[0164] The mixed slurry was placed in a microwave ball mill for ball milling at a heating temperature of 70° C. to obtain a dispersed slurry;

[0165] The dispersed slurry is dried at a drying temperature of 80°C in a vacuum drying oven. Drying in a vacuum is to prevent contamination by impurities during the drying process to obtain a precursor;

[0166] The precursor was transferred to a tube furnace and pre-sintered in an air atmosphere at a temperature of 600 °C, a sintering time of 2 h, and a heating rate of 2 °C / min.

[0167] The pre-sintered body is subjected to secondary sintering at a sintering temperature of 900°C and a sintering time of 6 h;

[0168] The sintered solid electrolyte sintered body was subjected to roller pressing and air flow pulverization treatment at an air pressure of 0.9 MPa to obtain the LATP solid electrolyte.

[0169] Comparative Example 1

[0170] Weigh lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate, and lutetium trioxide: 1.924g, 5.440g, 0.612g, 13.800g, and 0.1122g (Li2CO3:TiO2:Al2O3:NH4H2PO4:Lu2O3=1.3:3.4:0.3:6:0.11) respectively, and mix them evenly after ball milling.

[0171] 65.328 g of ethanol was added to obtain a mixed slurry;

[0172] The mixed slurry is placed in a microwave ball mill for ball milling at a heating temperature of 70° C. to obtain a dispersed slurry; the dispersed slurry is dried at a drying temperature of 80° C. The drying equipment is a vacuum drying oven. Drying in a vacuum is to prevent contamination by impurities during the drying process to obtain a precursor;

[0173] The precursor was transferred to a tube furnace and pre-sintered in an air atmosphere at a temperature of 600 °C, a sintering time of 2 h, and a heating rate of 2 °C / min.

[0174] The sintered solid electrolyte sintered body was subjected to roller pressing and air flow pulverization treatment at an air pressure of 0.7 MPa to obtain the LATP solid electrolyte.

[0175] LATP was added to LCO at a mass ratio of 0.5%, and the mixture was dry-milled to prepare CR2032 button cells as lithium battery positive electrode materials.

[0176] Comparative Example 2

[0177] Weigh lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate, and lutetium trioxide: 1.924g, 5.440g, 0.612g, 13.800g, and 0.1122g (Li2CO3:TiO2:Al2O3:NH4H2PO4:Lu2O3=1.3:3.4:0.3:6:0.11) respectively, and mix them evenly after ball milling.

[0178] 65.328 g of ethanol was added to obtain a mixed slurry;

[0179] The mixed slurry is placed in a microwave ball mill for ball milling at a heating temperature of 70° C. to obtain a dispersed slurry; the dispersed slurry is dried at a drying temperature of 80° C. The drying equipment is a vacuum drying oven. Drying in a vacuum is to prevent contamination by impurities during the drying process to obtain a precursor;

[0180] The precursor was transferred to a tube furnace and pre-sintered in an air atmosphere at a temperature of 500 °C, a sintering time of 2 h, and a heating rate of 4 °C / min.

[0181] The sintered solid electrolyte sintered body was subjected to roller pressing and air flow pulverization treatment at an air pressure of 0.7 MPa to obtain the LATP solid electrolyte.

[0182] LATP was added to LCO at a mass ratio of 0.5%, and the mixture was dry-milled to prepare CR2032 button cells as lithium battery positive electrode materials.

[0183] Comparative Example 3

[0184] Weigh lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate, and lutetium trioxide: 1.924g, 5.440g, 0.612g, 13.800g, and 0.1122g (Li2CO3:TiO2:Al2O3:NH4H2PO4:Lu2O3=1.3:3.4:0.3:6:0.11) respectively, and mix them evenly after ball milling.

[0185] 65.328 g of ethanol was added to obtain a mixed slurry;

[0186] The mixed slurry is placed in a pot mill for ball milling to obtain a dispersed slurry;

[0187] The dispersed slurry is dried at a drying temperature of 80°C in a vacuum drying oven. Drying in a vacuum is to prevent contamination by impurities during the drying process to obtain a precursor;

[0188] The precursor was transferred to a tube furnace and pre-sintered in an air atmosphere at a temperature of 700 °C, a sintering time of 2 h, and a heating rate of 3 °C / min.

[0189] The sintered solid electrolyte sintered body was subjected to roller pressing and air flow pulverization treatment at an air pressure of 0.7 MPa to obtain the LATP solid electrolyte.

[0190] LATP was added to LCO at a mass ratio of 0.5%, and the mixture was dry-milled to prepare CR2032 button cells as lithium battery positive electrode materials.

[0191] Comparative Example 4

[0192] Weigh lithium carbonate, titanium dioxide, aluminum oxide, and ammonium hydrogen phosphate: 1.924 g, 5.440 g, 0.612 g, and 13.800 g (Li2CO3:TiO2:Al2O3:NH4H2PO4:Lu2O3=1.3:3.4:0.3:6) respectively, and mix them evenly after ball milling.

[0193] 65.011 g of ethanol was added to obtain a mixed slurry, and after mixing, the raw material particles were dispersed using ultrasound for 30 min;

[0194] The mixed slurry was placed in a microwave ball mill for ball milling at a heating temperature of 70° C. to obtain a dispersed slurry;

[0195] The dispersed slurry is dried at a drying temperature of 80°C in a vacuum drying oven. Drying in a vacuum is to prevent contamination by impurities during the drying process to obtain a precursor;

[0196] The precursor was transferred to a tube furnace and pre-sintered in an air atmosphere at a temperature of 600 °C, a sintering time of 2 h, and a heating rate of 2 °C / min.

[0197] The pre-sintered body is subjected to secondary sintering at a sintering temperature of 900°C and a sintering time of 6 h;

[0198] The sintered solid electrolyte sintered body was subjected to roller pressing and air flow pulverization treatment at an air pressure of 0.7 MPa to obtain the LATP solid electrolyte.

[0199] Table 1 Battery performance test results of Examples 1-3 and Comparative Examples 1-3

[0200]

[0201] Table 2 Test results of battery performance of Examples 4-7 and Comparative Example 4 doped with different lutetium contents

[0202]

[0203] Table 3 Battery performance test results of Examples 8-10

[0204]

[0205] As can be seen from Table 1, compared with Comparative Example 1, Example 2 is compared with Comparative Example 2, and Example 3 is compared with Comparative Example 3, the secondary sintering step is omitted. The battery performance of Comparative Example 1, Comparative Example 2 and Comparative Example 3 in terms of the first charge specific capacity, discharge specific capacity, first coulombic efficiency and capacity retention rate (100 times) are all reduced, indicating that after the high-temperature secondary sintering, the obtained lutetium-doped LATP solid electrolyte structure is more stable.

[0206] from Figures 2 to 6 It can be seen that the capacity retention rate of the battery with lutetium-doped LATP solid electrolyte is improved.

[0207] As can be seen from Table 2, compared with Comparative Example 4, the first-cycle discharge capacity and capacity retention rate (100 times) of the battery of the LATP solid electrolyte doped with lutetium in Examples 4-6 with a content of lutetium doped in the range of 0.5%-3% are improved, the impedance is reduced, and the ionic conductivity is increased, indicating that by doping lutetium with the LATP solid electrolyte, lutetium expands the skeleton of the LATP solid electrolyte structure, thereby improving the ionic conductivity of the LATP solid electrolyte in the battery, which is beneficial to reducing the impedance of the battery; compared with Example 6 and Example 7, when the content of lutetium doping is too much, the skeleton structure of the LATP solid electrolyte is destroyed, thereby reducing the first-cycle discharge capacity and capacity retention rate (100 times) of the battery of the LATP solid electrolyte, the ionic conductivity is reduced, and the impedance of the battery is relatively high.

[0208] It can be seen from Table 3 that, compared with Examples 8-10, the pressure of airflow fragmentation affects the particle size of the LATP solid electrolyte, and the particle size of the obtained LATP solid electrolyte decreases as the airflow pressure increases.

[0209] The above-mentioned embodiments only express several implementation methods of the present disclosure, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the disclosed patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present disclosure, and these all belong to the protection scope of the present disclosure. Therefore, the protection scope of the disclosed patent shall be subject to the attached claims.

Claims

1. A method for preparing a LATP solid electrolyte for positive electrode material, characterized in that: The steps include: Mixing lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate and lutetium trioxide to obtain a mixed powder; adding an alcohol solvent to the mixed powder to obtain a mixed slurry; Performing a dispersion treatment on the mixed slurry to obtain a dispersed slurry; Drying the dispersed slurry to obtain a precursor; Pre-sintering the precursor at a temperature of 500° C. to 700° C. for a time of 2 h to 3 h to obtain a pre-sintered body; Performing secondary sintering on the pre-sintered body, wherein the secondary sintering temperature is 800° C.-1300° C., and the secondary sintering time is 2 h-10 h, to obtain a solid electrolyte sintered body; The solid electrolyte sintered body is crushed to obtain the LATP solid electrolyte.

2. The method for preparing the LATP solid electrolyte according to claim 1, characterized in that: Before mixing lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate and lutetium trioxide to obtain a mixed powder, the following steps are also included: The lithium carbonate, titanium dioxide, aluminum oxide, ammonium hydrogen phosphate and lutetium trioxide are ball-milled separately.

3. The method for preparing the LATP solid electrolyte according to claim 1, characterized in that: The added amount of lutetium trioxide is 0.5%-3%.

4. The method for preparing the LATP solid electrolyte according to claim 1, characterized in that: The mixed slurry is dispersed to obtain a dispersed slurry, comprising the following steps: The mixed slurry is subjected to microwave-assisted ball milling, the heating temperature of the microwave-assisted ball milling is 50° C.-80° C., and the ball milling time is 4 h-10 h.

5. The method for preparing the LATP solid electrolyte according to claim 4, characterized in that: Before the mixed slurry is subjected to microwave-assisted ball milling, an alcohol solvent is added to the mixed powder to obtain the mixed slurry, and the following steps are also included: The mixed slurry is subjected to ultrasonic dispersion, and the dispersion time is 30 min-60 min.

6. The method for preparing the LATP solid electrolyte according to claim 1, characterized in that: The alcohol solvent is at least one of ethanol, isopropanol and propanol.

7. The method for preparing the LATP solid electrolyte according to claim 1, characterized in that: The solid electrolyte sintered body is crushed to obtain the LATP solid electrolyte, which includes the following steps: Rolling the solid electrolyte sintered body; The solid electrolyte sintered body after rolling is subjected to air flow milling to obtain the LATP solid electrolyte.

8. The method for preparing the LATP solid electrolyte according to claim 7, characterized in that: The pulverizing pressure of the air flow pulverization is 0.4MPa-0.9MPa, and the particle size D50 of the LATP solid electrolyte is 200nm-300nm.

9. A LATP solid electrolyte for positive electrode material, characterized in that: The LATP solid electrolyte for positive electrode material is prepared by the preparation method of any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: The invention comprises a negative electrode sheet, a positive electrode sheet and a separator located between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet contains a positive electrode material, and the positive electrode material contains the LATP solid electrolyte for the positive electrode material as described in claim 9.

Citation Information

Patent Citations

  • Lithium titanium aluminum phosphate solid electrolyte material and preparation method thereof

    CN111233458A

  • Method for synthesizing lithium titanium aluminum phosphate

    CN116986893A

Cited By

  • Membrane based on fast ion conductor and preparation method and application thereof

    CN120749356A